علم المعاني في كتاب البلاغة الواضحة لعلي الجارم ومصطفي أمين : دراسة تقويمية من حيث الأهداف والمحتوى وطريقة العرض والتقويم - Akhsan Akhsan (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
The balaghah Wadhihah written by Ali al Jarim and Mustofa Amin is one of the famous books used by many pesantren in Indonesia. As a book that discusses the knowledge of Balaghah, this book contains about three sciences which are the basic pillars of Balaghah, namely Ilmu Bayan, Ilmu Badi’ and Ilmu Ma'ani. This research is an evaluative descriptive study. This study aims to evaluate the book Balaghah Wadhihah by Ali al Jarim and Musthafa Amin in terms of Ilmu Ma'ani to what extent this book has met the standards as a good textbook that can be used by students. This study will focus on evaluating aspects of the objectives, content, method of presentation and evaluation in the form of exercises or tests contained in the book.